Biosynthesis of silver nanoparticles using silver nitrate through biotransformation - Makesh Kumar. B1; V. Ganesan2, G. Pandiarajan1*, Govindaraj. R3 , (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">The development of appropriate processes for the synthesis of nanoparticles is an important aspect of nanotechnology. In the present study, fungus mediated synthesis of silver nanoparticles using Fusarium oxysporum has been investigated. The fungal mat was raised in MGYP broth and were transferred to silver nitrate aqueous solution for 72 hrs and analysed for the appearance of silver nanoparticles. These particles exhibited a new ÃŽÂ»max in the visible region as observed from the absorption spectrum. The plasmon peak was observed at 440nm. These nanoparticles were further characterized by FTIR and SEM analysis. There was a shift in peak at 1635 cm-1 when compared to the silver nitrate solution. SEM analysis showed that the silver nanoparticles produced in the present study were of varying morphology and ranged in size from 20-70nm. However further studies regarding EDS, XRD, NMR, TEM, AFM are confirmed to strengthen the present findings. Moreover, size controlled production of silver nanoparticles also confirmed further studies regarding the optimization of the medium and culture conditions.